'Music's a Family Thing': Cultural Socialisation and Parental Transference. (December 2015) - Reeves, Aaron
While parental encouragement or parent-led consumption transmits cultural practices from parents to children, the reasons parents provide regarding why they encourage cultural engagement remains unclear. Using music as a case study, and through analysing semi-structured interviews, this research explores how parents express and actualise their desire for their children to learn to play a musical instrument. Results suggest that respondents do not strongly associate musical practice with developing valued character traits nor with social or educational attainment. Instead, parental encouragement to play music is shaped by family ties and the parental perception of 'natural' talent in their children. Parental perception of natural talent is most common among parents who themselves play an instrument and among those parents who play music with their children. Family and musicality are the most commonly cited reasons for encouraging music and these are found among all educational groups. Without dismissing the importance of social position, this evidence suggests that parents articulate their preferences toward musical participation in terms of familial cohesion and shared identity.